Coronary computed tomography angiography assessment of relationship between right coronary artery-aorta angle and the development of coronary artery disease - Geerlings-Batt, Jade; Sun, Zhonghua (AME Publishing Company, 2023)
Whilst a correlation has been established between wide left main coronary artery bifurcation (LAD-LCx) angle (>80º) and the development of coronary artery disease (CAD), this retrospective, causal-comparative pilot study aimed to explore whether a relationship exists between right coronary artery (RCA)-aorta angle and CAD. Thirty normal cases were identified via radiology reports and selected as the control group with coronary computed tomography angiography (CCTA) scans performed on a 320-slice computed tomography (CT) scanner. Thirty CAD cases were selected with invasive coronary angiography performed to confirm the degree of stenosis, and CCTA performed on dual source and 320-slice CT scanners. An independent sample T-test was used to compare the differences in coronary angles between the normal and CAD group, and analysis of variance was used to assess for significant differences between coronary angles in normal and CAD subgroups. Coronary angle measurements were conducted by two independent assessors with high intraclass correlation (r=0.971-0.998, p<0.001). RCA-aorta angle measurements were significantly larger in the normal group (87.47°, 95% CI: 79.31°-95.78°) compared to the CAD group (76.82°, 95% CI: 67.82°-85.61° p=0.05). No significant difference was found between RCA-aorta angle and degree of coronary stenosis (p=0.75). This study suggests a relationship between narrow RCA-aorta angle and CAD.